2019
DOI: 10.3390/antiox8090395
|View full text |Cite
|
Sign up to set email alerts
|

Maltol Improves APAP-Induced Hepatotoxicity by Inhibiting Oxidative Stress and Inflammation Response via NF-κB and PI3K/Akt Signal Pathways

Abstract: Maltol, a food-flavoring agent and Maillard reaction product formed during the processing of red ginseng (Panax ginseng, C.A. Meyer), has been confirmed to exert a hepatoprotective effect in alcohol-induced oxidative damage in mice. However, its beneficial effects on acetaminophen (APAP)-induced hepatotoxicity and the related molecular mechanisms remain unclear. The purpose of this article was to investigate the protective effect and elucidate the mechanisms of action of maltol on APAP-induced liver injury in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…APAP overdose-induced liver hepatotoxicity is a well-known drug-induced liver injury. It is the most common cause of acute liver failure in several countries, replacing viral hepatitis [ 36 ]. Extensive oxidative stress is a characteristic of APAP hepatotoxicity during APAP metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…APAP overdose-induced liver hepatotoxicity is a well-known drug-induced liver injury. It is the most common cause of acute liver failure in several countries, replacing viral hepatitis [ 36 ]. Extensive oxidative stress is a characteristic of APAP hepatotoxicity during APAP metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro studies showed that maltol played a role as an immune modulator during inflammatory responses. Maltol also influences the anti-oxidant activity ( 22 ) by scavenging free radicals generated during oxidative stress ( 20 ). Oxidative stress incurred during an inflammatory response may trigger the overproduction of reactive oxygen species, which can form a vicious circle resulting in tissue damage in intestinal epithelia and liver tissues ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study ( 19 ), dietary feeding of the Bacillus subtilis 1781 strain induced the alteration of chicken gut metabolites which was associated with the growth- and immune-promoting effects of dietary B. subtilis 1781 strain in chickens. Among the highly altered gut metabolites, maltol was one of the significantly increased metabolites that we selected for further studies since maltol mediates various physiological functions associated with anti-oxidant ( 20 ) and anti-carcinogen ( 21 ) activities and reduces inflammatory responses ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The AKT signaling pathway plays an essential role against I/R injury by regulating proapoptotic signals, inflammation and ROS ( Li Q. et al, 2019 ). Oxidative stress-induced cell apoptosis is due to AKT dysfunction and NFκB upregulation ( Wang et al, 2019 ). JNK/NFκB is involved in myocardial I/R-induced apoptosis ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%